Discussion on possibility of community-based waste management views from citizen environmental consciousness: A case of rural area in Karang Joang Village, Balikpapan Indonesia) - Indriyani Rachman, Toru Matsumoto (Universitas Andalas, 2017)
The habit of Karang Joang people is throwing garbage, inherited from generation to generation. Most of treating’s their garbage are by burning it in the yard, throwing into the garden or the river. The transportation to take garbage that isn’t intensive by city officers and the lack of knowledge in managing the garbage greatly affects the pollution condition of the air, soil and water in the village. This research focuses on the patterns of society in treating organic waste and inorganic. Environmental conditions in the village to make some attention from the city government Balikpapan. Because the village is located in a protected forest manggar should be kept clean. We distributed questionnaires to 500 housewives that are living in 12 areas near the river. We interviewed one of the small shop and 5 housewives about what they buy and how dispose of waste in one day. Approximately 5-7 sachet plastics and around 200-300 grams of organic garbage. And approximately one drum of water is used for one family. Six months after distributing questionnaires and analyzing, we held a workshop with theme on the importance of eco-friendly living, composting of organic garbage, and counseling about bank of garbage program for 32 leaders in the village. Then we try to find solutions about how to build the consciousness and management in solid waste. In this study, some possible solutions have been presented by transfer environmental technologies